Pendidikan Kewarganegaraan di Era Revolusi 4.0 - Renata Nur Annisa; Dinie Anggraeni Dewi (IJoIS: Indonesian Journal of Islamic Studies, 2021)
The golden generation (Generation 4.0) is a period where human groups at that time have a uniqueness that can characterize themselves and change history or times. The golden generation will take place in 2024. In the era of revolution 4.0, the golden generation must be prepared to face the challenges of its time, such as implementing development with existing and future resources, such as Human Resources (HR), and maintaining sustainability and sustainability. of development and these resources. When it is linked between generation and development, the existence of a generation will not be separated from the character and characteristics of the population of a nation and its conditions, because every human being has his own character and characteristics, therefore the formation of a golden generation will not be separated from education. . Because through education, especially civic education, the character of the nation can be formed. Such as, independence will be realized, Cultural Values ​​can be embedded, and can know how the nature and character of each of them.